SOCIAL CLASS AND PSYCHOTHERAPY: A CRITICAL READING OF THOMAS SZASZ’S THE ETHICS OF PSYCHOANALYSIS - du Plessis, Rory (PINS-Psychology in Society, 2025)
This paper aims to offer a critical reading of Thomas S. Szasz’s The ethics of psychoanalysis: The theory and method of autonomous psychotherapy (1965 / 1988a). In particular, the critical reading is focused on revealing and investigating the presence of attitudinal biases and beliefs pertaining to the social class of psychotherapy. It will be argued that in Szasz forwarding his thesis, a number of statements regarding social class are raised. In particular, and for the purposes of this paper, the key focus will be an investigation of Szasz’s proclamation that the poor and uneducated do not need psychoanalysis but require freedom, knowledge and skills. The paper will argue that this statement may not necessarily be presenting an attitudinal bias or belief against the poor and uneducated. Rather, Szasz is professing the nature and limitations of psychotherapy. Nonetheless, Szasz’s text still reflects attitudinal biases through the disapproval of the efforts made by Sigmund Freud to make psychotherapy available to all people.